Macerals of Shengli Lignite in Inner Mongolia of China and Their Combustion Reactivity - Ying Yue Teng; Yu Zhe Liu; Quan Sheng Liu; Chang Qing Li (Journal of Chemistry)
The macerals, including fusinitic coal containing 72.20% inertinite and xyloid coal containing 91.43% huminite, were separated from Shengli lignite using an optical microscope, and their combustion reactivity was examined by thermogravimetric analysis. Several combustion parameters, including ignition and burnout indices, were analyzed, and the combustion kinetics of the samples were calculated by regression. Fusinitic coal presented a porous structure, while xyloid coal presented a compact structure. The specific surface area of fusinitic coal was 2.5 times larger than that of xyloid coal, and the light-off temperature of the former was higher than that of the latter. However, the overall combustion reactivity of fusinitic coal was better than that of xyloid coal. The combustion processes of fusinitic and xyloid coals can be accurately described by both the homogeneous model and the shrinking core model. The features of xyloid coal agree with the shrinking core model when its conversion rate is 10%–90%. The activation energy of fusinitic coal during combustion can be divided into three phases, with the middle phase featuring the highest energy. The activation energy of xyloid coal is lower than that of fusinitic coal in the light-off phase, which may explain the low light-off temperature of this coal.